Stem cell bioprocessing - Mantalaris, Sakis (Henry Stewart Talks, 2007)
The development of bioprocessing technology: control, reproducibility, automation, validation and safety, The bioprocessing environment, Bioprocessing issues, Bioprocessing operating system, Bioprocessing culture parameters: media, pH, DO and cytokines, Basic types of bioreactors: operating modes of bioreactors, bioreactor design criteria and bioreactor types, Cell culture systems, Bioreactor system design requirements, Design of experiments (DOE), Types of designs and experiments, DOE cell culture issues and concerns